Existence: Eight LGBTQIA+ Inclusive ELT Resources by Peter J. Fullagar - Polastri, Vanesa (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This materials review article analyses Existence: Eight LGBTQIA+ Inclusive ELT Resources, a handbook written by Peter J. Fullagar. The lack of representation of the LGBTQIA+ community in mainstream coursebooks for teaching English drove its author to design inclusive lessons that were later put together in this first collection ranging from A2 to C1 in the CEFR. The topics discussed, the images incorporated, as well as the words chosen to address people and their lifestyles are among its positive aspects. The handbook also promotes communication, critical thinking and research skills. It is indeed an invaluable contribution to ELT materials since, for a change, it makes LGBTQIA+ people―in all their colours, shapes, sizes, abilities, origins, economic situations―visible and, therefore, conceived as worthy in the eyes of others and in their own.